Strategies of racial identity negotiation of Brazilian immigrants in the United States - Pereira de Brito , Edvan (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
The present study focuses on certain aspects of the process of racial identity negotiation of Brazilian immigrants in the United States, taking into account the sociocultural context of the U.S. in relation to the Brazilian reality. The study of identity has had considerable attention from scholars from many research fields due to its increasing importance in the last decades. The crossing of borders brings about new realities and cultures, in which people are required to embark on a constant process of identity negotiation. In this process of redefinition of identities one also must consider the relational feature embedded in the concept of identity. Based on a bibliographical analysis, this paper presents a synthesis of theracial identity negotiation strategies of Brazilian immigrants in the United States, discussing them in light of the sociocultural aspects involved in the process